A dopamine receptor D2 genetic polymorphism associated with transition to mental disorders in a cohort of individuals with at-risk mental state for psychosis - Marques, Julia Hatagami; Talib, Leda Leme; Hortêncio, Lucas; Andrade, Julio Cesar; Alves, Tania Maria; Serpa, Mauricio Henriques; Yamamoto, Guilherme Lopes; van de Bilt, Martinus Theodorus; Rössler, Wulf; Gattaz, Wagner Farid; Loch, Alexandre Andrade (Revista brasileira de psiquiatria, 2023)
We aimed to test the association of 45 single nucleotide polymorphisms (SNPs) and transition to psychiatric disorders in a cohort of individuals with at-risk mental state for psychosis (UHR). Through general population screening, 88 non-help-seeking UHR subjects and 130 healthy control individuals were genotyped for 45 SNPs related to psychosis. They were followed up for a mean of 2.5 years, and conversion to psychotic and to general psychiatric disorders was assessed. Genotype frequencies between controls, converters and non-converters were analyzed. There were no differences in sociodemographics between controls and UHR. Also, UHR converters and non-converters had no differences in their baseline symptoms scores. The rs6277, a dopamine receptor D2 gene (DRD2) SNP, was significantly related to UHR who transitioned to psychosis (p<0.001) and to UHR who transitioned to any psychiatric disorders (p=0.001), when compared to UHR who did not transition. The rs6277 T allele was related to psychiatric morbidity in a dose-response fashion, being significantly more frequent in UHR-converters than UHR-non-converters and control subjects (p=0.003). Our findings suggest that rs6277 could potentially constitute a genetic marker of transition to psychiatric disorders in subjects with at risk mental states, warranting further investigation with larger samples.